Reliability And Operational Performance Indicators Of Expanded Functional Capability Electromagnetic Current Converters (Texas Journal of Engineering and Technology, 2025)
In general, reliability refers to the ability of an object (equipment, system components) to perform its designated functions within a specified volume and time under the observed conditions while maintaining its operational state within the intervals specified in normative documents